2021
DOI: 10.1111/bjhp.12549
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative aspects of mental health after unspecified living kidney donation: A cohort study

Abstract: Objectives. Unspecified donors give a kidney to a stranger with end-stage kidney failure. There has been little research on the long-term impact of unspecified donation on mental health outcomes. The aim of this study was to assess the positive and negative aspects of mental health among unspecified donors.Design. We invited all unspecified donors who donated a kidney between 2000 and 2016 at our centre to participate in an interview and to complete validated questionnaires. Methods. We measured positive menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Nevertheless, it has also been reported that the donation was experienced as life interrupting or as a source of interpersonal stress (8)(9)(10)(11)(12). In addition, some UKDs complained about the intensity and length of the donor assessment procedure and the long waiting time before the actual donation (9)(10)(11)(12)(13)(14). Although the aforementioned studies have provided reassuring evidence with regard to the experiences of UKDs, they cannot simply be generalized to the Netherlands, because of different healthcare systems across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has also been reported that the donation was experienced as life interrupting or as a source of interpersonal stress (8)(9)(10)(11)(12). In addition, some UKDs complained about the intensity and length of the donor assessment procedure and the long waiting time before the actual donation (9)(10)(11)(12)(13)(14). Although the aforementioned studies have provided reassuring evidence with regard to the experiences of UKDs, they cannot simply be generalized to the Netherlands, because of different healthcare systems across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there is not a strong body of evidence affirming the psychological wellbeing of UKDrs, neither is there evidence of an underlying psychopathology. Previous research demonstrates that UKDrs have positive outcomes [ 34 ] and equivalent psychological outcomes to SKDrs [ 9 , 35 ]. Motives are honourable, however the evidence to date for the personal benefit of UKD is mixed [ 36 ], and studies reporting benefits are mainly retrospective [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Few studies have assessed donor characteristics that are associated with worse mental health outcomes postdonation, 14 and there has been a noted decrease in mental health-related quality of life 3 mo after donation with a trend toward baseline by approximately 12 mo after donation. 15 , 16 Furthermore, there are limited data that characterize the mental health of living donors predonation, 14 , 16 , 17 and no data describing the mental health of prospective living donor applicants. It is important to consider the self-reported mental health conditions that applicants report on their intake screening forms, such as anxiety and depression, as well as the medications they report taking.…”
mentioning
confidence: 99%